Demarcation of the Boundaries of the Central Asian Desert Natural Focus of Plague of Kazakhstan and Monitoring the Areal of the Main Carrier, Rhombomys opimus - Z. Zh. Abdel; T. K. Erubaev; G. Zh. Tokmurzieva; B. K. Aimakhanov; Zh. S. Dalibaev; R. S. Musagalieva; Z. B. Zhumadilova; V. G. Meka-Mechenko; T. V. Meka-Mechenko; A. M. Matzhanova; A. A. Abdrasilova; S. K. Umarova; et al. (Проблемы особо опасных инфекций, 2021)
The aim of the study was to clarify the boundaries of the Central Asian natural plague focus of Kazakhstan and the modern boundaries of the areal of the great gerbil (Rhombomys opimus) in order to improve epizootiological monitoring and increase the effectiveness of preventive (anti-epidemic) measures.Materials and methods. Data from the epizootiological monitoring of the great gerbil populations in 14 autonomous foci of the Central Asian desert natural plague focus in the Republic of Kazakhstan between 2010 and 2020 were used for the analysis. An epizootiologic survey of an area of 875350 km2 was carried out. When processing the data, epidemiological, epizootiological, statistical research methods, as well as GIS technologies were used.Results and discussion. An increase in the total area of the Central Asian desert natural plague focus of the Republic of Kazakhstan by 79710 km2 (9.98 %) has been established for the period of 1990–2020. It is noted that the change in the area of plague-enzootic territory was a consequence of the ever changing areal of the main carrier of plague pathogen – the great gerbil – under the influence of climatic and anthropogenic factors. The most significant changes were found in the southeastern part of the plague-enzootic territory, including those for the Betpakdala (50 %), Balkhash (34.3 %), Taukum (13.3 %) and Mojynkum (0.32 %) autonomous foci. The area of the Aryskum-Dariyalyktakyr autonomous focus decreased by 2100 km2 (4 %). In 2000–2002, new Alakol’sky and Ili intermountain autonomous foci with a total area of 26759 km2 were discovered. It is shown that due to the regression of the Aral Sea, the areal of the great girbil expanded and the area of the North Aral and Kyzylkum natural plague foci increased by 10500 km2 (29.2 %) and 560 km2 (0.4%), respectively. The areas of the Aral-Karakum and UralEmba desert autonomous foci, on the contrary, decreased by 2000 km2 (2.6 %) and 12300 km2 (17.6 %), respectively. Passportization and landscape-epizootiologic zoning of the territory of the Central Asian desert natural plague focus of the Republic of Kazakhstan has been completed.